Unlocking biodiversity data: Prioritization and filling the gaps in biodiversity observation data in Europe. (May 2018) - Wetzel, Florian T.; Bingham, Heather C.; Groom, Quentin; Haase, Peter; Kõljalg, Urmas; Kuhlmann, Michael; Martin, Corinne S.; Penev, Lyubomir; Robertson, Tim; Saarenmaa, Hannu; Schmeller, Dirk S.; Stoll, Stefan; et al.
Abstract: Large quantities of biodiversity data are required to assess the current status of species, to identify drivers of population and distributional change, and to predict changes to biodiversity under future scenarios. Nevertheless, currently-available data are often not well-suited to these purposes. To highlight existing gaps, we assess the availability of species observation data in Europe, their geographic and temporal range, and their quality. We do so by reviewing the most relevant sources for European biodiversity observation data, and identifying important barriers to filling gaps. We suggest strategies, tools and frameworks to continue to fill these gaps, in addition to producing data suitable for generating Essential Biodiversity Variables (EBVs). Our review of data sources shows that only around a third of data-providers provide unrestricted data access. Particularly large geographic gaps exist in Eastern European countries and many datasets are not suitable for generating EBVs due to the absence of long-term data. We highlight examples built on recent experiences from large data integrators, publishers and networks that help to efficiently improve data availability, adopt open science principles and close existing data gaps. Future strategies must urgently consider the needs of relevant data stakeholders, particularly science- and policy-related needs, and provide incentives for data-providers. Hence, sustainable, long-term infrastructures and a European biodiversity network are needed to provide such efficient workflows, incentives for data-provision and tools. Highlights: Only around a third of data providers provide unrestricted data access - increased open access is needed. There are large geographic gaps in Eastern Europe, the Caucasus and gaps related neglected taxonomic groups (e.g. reptiles). We highlight examples that help to efficiently improve data availability, adopt open science principles and close existing gaps. Incentives for data providers and sustainable, long-term infrastructures and a European biodiversity network is urgently needed.